Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Microelectronic Applications of Chemical Mechanical Planarization 2007
DOI: 10.1002/9780470180907.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Key Chemical Components in Metal CMP Slurries

Abstract: Chemical-mechanical planarization (CMP) slurries can be classified into two general categories according to their applications: metal CMP slurry and nonmetal CMP slurry. Two most important metals incorporated into IC chip manufacturing via CMP are W and Cu. Depending upon integration schemes, a metal CMP slurry may or may not carry out the function of removing the film(s) immediately below the overburden metal such as cap, adhesion, and barrier layers. For tungsten CMP, a single-step slurry is typically used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…This trend followed the indentation mechanism, which predicts higher MRR with larger particle size. 16 By contrast, an earlier study of W CMP by Bielmann et al 17 revealed an opposite trend, which was also observed by Lu et al 18 in Cu/Ta CMP. However, both articles focused on CMP slurries with larger particle sizes and higher abrasive contents than the present slurry formulation.…”
Section: Methodsmentioning
confidence: 49%
“…This trend followed the indentation mechanism, which predicts higher MRR with larger particle size. 16 By contrast, an earlier study of W CMP by Bielmann et al 17 revealed an opposite trend, which was also observed by Lu et al 18 in Cu/Ta CMP. However, both articles focused on CMP slurries with larger particle sizes and higher abrasive contents than the present slurry formulation.…”
Section: Methodsmentioning
confidence: 49%
“…It is a major drawback, especially in the case of W-CMP slurry, for which the chemical composition plays a major role in the chemical and mechanical polishing. As reviewed by several authors, the chemical composition of W-CMP slurry is a determining factor in obtaining uniform and non-defective polishing [5,24,25]. Moreover, in our case, recycling slurry has to be directly operational and all the settings related to the polishing process have to stay unchanged.…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that the reduction of particles agglomeration prevents the formation of defects [44]. Moreover, surfactants are used as dissolution inhibitors of the metal surface in chemical mechanical polishing [5,44]. In the case of tungsten CMP, this kind of inhibitor is not particularly required because of the low corrosive potential of tungsten [30], but could help to decrease the excess of dissolution mechanism for tungsten slurry recycling [46,47].…”
Section: Effect Of a Mixture Of Surfactants On Cmp Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…From the Pourbaix diagram shown [25] in Figure 7.14, copper forms the oxides Cu 2 O and CuO, depending on the process conditions. From the Pourbaix diagram shown [25] in Figure 7.14, copper forms the oxides Cu 2 O and CuO, depending on the process conditions.…”
Section: Chemical Processesmentioning
confidence: 99%